Analysis on Evolution of Strategies: Global Multinational Companies in China - Salazar, Ronald J.; Wang, Jifu; Zhao, Jinhua (New Innovations in Economics, Business and Management Vol. 7, 2022)
This is an examination of the evolution of the strategies of large multinational corporations doing business in China. Based on a survey of large firms, we classified the strategic posture of MNC subsidiaries in China into four discrete frames using the TOWS approach (Weirich, 1982). The strategic motives that inspire MNCs to engage in FDI have been a source of discussion for many years among researchers. The findings of our study, which used the TOWS approach, enabled us to identify a trend in strategic evolution. We discover that the primary investment motivation of MNS in China has shifted from "low labor cost" to " exploiting Chinese market." We report on the motivations, actions, and aspirations of the managers of the largest multinational subsidiaries operating in the country. The research results show that there is significant variation in the strategic posture exhibited by MNS. This difference is shown in each of the four frames. In the S-O quadrant MNS in China adopt a consistent developing strategy based on overall cost leadership.